The new Lumbar Spinal Fusion technique: Minimally Invasive Trans-psoas approach (Direct Lateral Interbody Fusion (DLIF®)) and a preliminary report of clinical and radiographic success in Bangkok Spine Academy - Buranakarl, Tayard; Jaisanuk, Kanoknard (The Bangkok Medical Journal, 2012)
OBJECTIVE. To study the preliminary results in 12 cases who underwent Direct Lateral Interbody Fusion (DLIF) in Bangkok Spine Academy. MATERIALS AND METHODS. The study of the preliminary results and retrospective chart review of collected clinical and radiographic outcomes in 12 patients who underwent Direct Lateral Interbody Fusion L1-L5 as a treatment for degenerative disc disease, degenerative scoliosis and/or degenerative spondylolisthesis. Clinical outcomes measured include Visual Analog Scale (VAS) and Radiographic outcome. RESULTS. Twelve patients underwent DLIF between February and July, 2012 with altogether twenty intervertebral disc levels treated. Most cases had indications of back pain with radiation to leg from nerve root compression. Two cases (16.6%) were back pain from a single level severe disc degeneration with signs of instability and unresolved by non-surgical treatment. Five cases (41.7%) were diagnosed with degenerative scoliosis and the other 5 (41.7%) were degenerative spondylolisthesis who did not respond to non-surgical treatment. Mean operative time was 70.6 (±17.7) minutes (mean ± standard deviation). Minimal surgical duration was 41.7 minutes for each level and maximum 110 minutes. Intraoperative blood loss averaged 81.7 mL. Initial pain scores in patient-reported questionnaires (VAS back, VAS legs) showed fast and lasting pain relief and improvement in daily activities. Mean VAS back scores decreased from 5.3 to 0.4. For leg pain assessment, mean VAS scores decreased from 6.3 to 0.3. at the 2 weeks visit. There was a mean correction of 7.9 to 3.2 degrees in segmental coronal plane in all instrumented levels. There was significant change in the overall coronal plane alignment of the lumbar spine. Increasing disc height at middle column 7.0 mm. There were no intraoperative complications. The bleeding during operation was much less than conventional surgery. Neurological examinations showed one patient to have Psoas weakness with anterior thigh numbness, both conditions resolving within 2 weeks. CONCLUSION. This preliminary short term report of DLIF at Bangkok Spine Academy shows as satisfactory and consistent results as other mini-opened transposes approaches. The benefits of this procedure are reducing leg and back pain, less blood loss, minimized soft tissue injury, wide safety margin of inadvertent complications, especially nerve root injuries, thus less likelihood for long term complications and for lumbar degenerative spine in cases of decompression and fusion.